Gratitude (shukr) group intervention for promoting college students’ well-being: A quasi-experimental study - Melati Sumari; Dini Farhana Baharudin; Amira Najiha Yahya; Yusni Mohamad Yusop (Social Sciences and Humanities Open)
This study examined the impact of a gratitude (shukr) group intervention on the well-being of college students. We hypothesised that participation in the intervention would increase feelings of well-being. A single-group quasi-experimental design with pre-test and post-test measures was employed. A convenience sample of 95 s-year college students consented to participate—the intervention, conducted over four weeks between November and December 2023, involved weekly gratitude group sessions. The Warwick-Edinburgh Mental Well-being Scale (WEMWBS) was used to assess well-being before and after the intervention. Descriptive statistics and paired sample t-tests were conducted to analyse the data. Qualitative data from participants' reflection reports were also thematically analysed for supportive evidence. Results indicated that post-test well-being scores were significantly higher than pre-test scores (p < .05). The findings suggest that the gratitude (shukr) group intervention significantly improved college students’ well-being.